Fighting assessment strategies: model evaluation and empirical evidences from a neotropical cricket - Oliveira, Gabriel Lobregat de (2018)
Animal contests usually end before the death of one of the rivals, and their resolution depends on the decision of the loser to withdraw. Evolutionary game theory models assume two major asymmetries between contestants as determinants for fighting success: fighting ability and motivation to win the contest. Different models propose strategies of how contestants assess information about these asymmetries in their decision to stay or leave the fight. The empirical evaluation of the relationship between proxies of fight- associated costs and fighting ability allows to discriminate which of these models explain better the contest behavior of species. Empirical studies also try to elucidate the mechanisms that contestants use to transmit information to the opponent by evaluating the information content of aggressive displays and other agonistic behaviors. In the first chapter of this thesis, we used individuals from simulated populations to establish contests that followed the predictions of different assessment strategies. We demonstrated that different offensive capacities (i.e. damage output) in injurious contests might generate similar results for different assessment models, hampering the discrimination of which model explain better the contests. We also showed that when contest behavioral phases follow different assessment strategies, the evaluation of overall contest alone hinders the detection of what assessment strategy is applied in the second phase, as every contest present the first phase, but not all contests escalate to the second phase. Thus, it is necessary to consider the offensive capacity of a species and the possibility of switching assessment between contest phases to correctly assign what assessment strategies explain the contest behavior of species. In the second chapter, we investigated the contest behavior of Melanotes ornata in order to elucidate what assessment strategy these crickets use. We showed that, as expected by the results of Chapter 1, a single assessment strategy does not explain the contest dynamics of this species. We found evidences that in the first contest phase, individual mutually assess each other and escalate to the second phase when their fighting abilities are similar. In the second contest phase, however, no fighting ability assessment appears to occur. We suggest that after escalation other asymmetries, like differences in motivation, may be more important to contest resolution. In the third chapter, we evaluated the information content of aggressive sound signals emitted by viindividuals in escalated phases. We show that sound parameters of aggressive song do not have any information about fighting ability. In counterpart, contestants with higher motivation showed a higher signaling effort along the contest and also displayed with a higher pulse rate. Thus, such signals contain information about motivational status of contestants and may be used in the assessment of opponent’s motivation in escalated fights.